Prognostic Comparison between cTACE and H101-TACE in Unresectable Hepatocellular Carcinoma (HCC): A Propensity-Score Matching Analysis - Man Yao; Simo Cheng; Xiaofeng Zhai; Hetong Zhao; Jing Hong; Xiaoyan Li; Yongbin Meng; Wei Chen (Applied Bionics and Biomechanics)
Background. Transarterial chemoembolization (TACE) is the most common treatment for patients with HCC who are unsuitable for radical therapies. Conventional TACE (cTACE) takes advantage of the preferential hepatic arterial supply of HCC for the targeted delivery of chemotherapeutic agents suspended in lipiodol, followed by embolization or reduction of arterial flow using various types of particles while sparing the surrounding liver parenchyma. Aims and Objectives. The current study is aimed at comparing the efficacy and safety profiles of transarterial infusion of recombinant human type-5 adenovirus (H101-TACE) with conventional transarterial chemoembolization (cTACE) in patients with unresectable hepatocellular carcinoma (HCC). Methods. Unresectable HCC patients that received H101-based TACE or cTACE from August 2018 to September 2021 were retrospectively evaluated. Propensity score matching (PSM) has a 1 : 1 ratio to eliminate possible confounder imbalances across cohorts. The main outcome was overall survival (OS), while secondary outcomes were progression-free survival (PFS) and tumor response. Results. This study included 111 patients classified across two cohorts: the H101-TACE cohort (n=37) and the cTACE cohort (n=74). Median OS within the H101-TACE cohort was 9.0 months longer than within the cTACE cohort before PSM (22.1 vs. 13.1 months, P=0.043) and 9.3 months longer following PSM (22.1 vs. 12.8 months, P=0.004). The median PFS within the H101-TACE cohort was 3.2 months longer compared to the cTACE cohort before PSM (6.5 vs. 3.3 months, P=0.046) and 2.5 months after PSM (6.5 vs. 4.0 months, P=0.012). The disease control rate for H101 and control cohorts was 81.1% and 59.5%, accordingly (P=0.039). Conclusion. The present study demonstrated that the H101-TACE is safe and efficient and can considerably enhance prognostic results for unresectable HCC compared to cTACE.